2004
DOI: 10.21000/jasmr04010174
|View full text |Cite
|
Sign up to set email alerts
|

Refinement of ADTI-WP2 Standard Weathering ProcEdures, and Evaluation of Particle Size and Surface Area Effects upon Leaching Rates: PART 2: PRACTICAL AND THEORETICAL ASPECTS OF LEACHING KINETICS

Abstract: Most previous coal mine drainage leaching studies have not investigated the effect of surface area, effects of elevated Pco 2 , which are typical of mine spoil, and solubility constraints on water chemistry. The leaching column and humidity cell tests were designed to evaluate the importance of these parameters. Surface area was examined on three rock types before and after leaching: the Brush Creek shale; a well-indurated calcareous sandstone; and a coal refuse. The surface area, as measured by BET, for the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…Regarding operational consistency of the method, large amounts of fine particles within specific zones of the leaching columns were found to impede uniform fluid flow and/or gas flow in this study, and similar problems with fines are described in Caruccio (1990, 1995) and Hornberger and Brady (1998). Regarding the determination of reaction kinetics, the importance of surface area to volume ratios is described in Part II of this paper (Brady et al, 2004), and significant differences in crushed particle size distributions and effective surface areas were found among the lithologic units tested in this study. Standardizing the particle size distribution in each leaching column promotes control of that variable at the start of the weathering test, and facilitates the evaluation of surface area and related kinetic variables after weathering.…”
Section: Second Year (2003) Weathering Test Resultsmentioning
confidence: 86%
See 2 more Smart Citations
“…Regarding operational consistency of the method, large amounts of fine particles within specific zones of the leaching columns were found to impede uniform fluid flow and/or gas flow in this study, and similar problems with fines are described in Caruccio (1990, 1995) and Hornberger and Brady (1998). Regarding the determination of reaction kinetics, the importance of surface area to volume ratios is described in Part II of this paper (Brady et al, 2004), and significant differences in crushed particle size distributions and effective surface areas were found among the lithologic units tested in this study. Standardizing the particle size distribution in each leaching column promotes control of that variable at the start of the weathering test, and facilitates the evaluation of surface area and related kinetic variables after weathering.…”
Section: Second Year (2003) Weathering Test Resultsmentioning
confidence: 86%
“…Whereas, the major factors controlling sulfate (and acidity) production from a rock sample with appreciable total sulfur content include particle size and surface area. These relationships are discussed in more detail in Brady et al (2004), Geidel (1979) and Hornberger and Brady (1998). column sizes upon analyte concentrations showed that mean and maximum alkalinity concentrations produced from the shale sample in the 6 inch column were not greater than those corresponding to the smaller column diameters.…”
Section: Second Year (2003) Weathering Test Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Initial development in phases I and II included evaluation of different test apparatus, effects of particle size, gas composition, leaching frequency and other variables. Phases I and II results are reported by Brady et al (2004) and Hornberger et al (2004). In Phase III, a standard column leaching protocol was used by eight commercial, government and university labs to test five rocks of different lithology, pyrite and carbonate content.…”
Section: Introductionmentioning
confidence: 99%
“…al., (2003Hornberger et. al., ( , 2005 and Brady et al, (2004). The final step to completing the development of the final draft of the ADTI-WP2 Leaching Column Method and publishing it in the Federal Register as a standard EPA method is a full inter-laboratory validation study in accordance with the ASTM D -2777 protocol.…”
mentioning
confidence: 99%